Cambridge O level Islamiyat paper 2 - Nishat, Hammad Ibn (Karachi : Bookmark publishing, 2019)
The Cambridge O Level Islamiyat Textbook for Paper 2 by Bookmark Publishing is a focused and comprehensive resource designed to help students prepare specifically for the Paper 2 section of the Cambridge O Level Islamiyat exam. The book is aligned with the Cambridge O Level Islamiyat syllabus and provides in-depth coverage of the key topics and themes that are tested in Paper 2, which generally focuses on Islamic history, thought, and practice.
Keywords: Islamiyat : Textbook paper 2; O level : 3rd edition